Human Pegivirus Infection and Lymphoma Risk: A Systematic Review and Meta-analysis. (31st October 2019) - Fama, Angelo; Larson, Melissa C; Link, Brian K; Habermann, Thomas M; Feldman, Andrew L; Call, Timothy G; Ansell, Stephen M; Liebow, Mark; Xiang, Jinhua; Maurer, Matthew J; Slager, Susan L; Nowakowski, Grzegorz S; et al.
Abstract: Background: Human pegivirus (HPgV) is a single-strand RNA virus belonging to the Flaviviridae. Although no definitive association between HPgV infection and disease has been identified, previous studies have suggested an association of HPgV viremia with risk of lymphomas. Methods: We conducted a systematic review and meta-analysis, including 1 cohort study and 14 case-control studies, assessing the association of HPgV viremia with adult lymphomas. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using a random-effects model, overall and by geographic region and lymphoma subtype. Results: The overall OR for lymphoma was 2.85 (95% CI, 1.98–4.11), with statistically significantly elevated ORs observed in 8 of 15 studies. There was a small amount of heterogeneity among studies ( I 2 = 28.9%; Q = 18.27, P = .16), and the funnel plot provided no evidence for publication bias. The strongest association with lymphoma risk was observed for studies from Southern Europe (OR, 5.68 [95% CI, 1.98–16.3]), whereas weaker ORs (with 95% CIs) were observed for studies from North America (2.24 [1.76–2.85]), Northern Europe (2.90 [.45–18.7), and the Middle East (2.51 [.87–7.27]), but all of similar magnitude. Participants with HPgV viremia had statistically significantly increased risks (OR [95% CI]) for developing diffuse large B-cell (3.29 [1.63–6.62]), follicular (3.01 [1.95–4.63]), marginal zone (1.90 [1.13–3.18]), and T-cell (2.11 [1.17–3.89]) lymphomas, while the risk for Hodgkin lymphoma (3.53 [.48–25.9]) and chronic lymphocytic leukemia (1.45 [.45–4.66]) were increased but did not achieve statistical significance. Conclusions: This meta-analysis supports a positive association of HPgV viremia with lymphoma risk, overall and for the major lymphoma subtypes. Abstract : In a meta-analysis of 15 studies, human pegivirus (HPgV) viremia was associated with an increased risk of lymphoma. As about 2% of US blood donors are viremic with HPgV at donation, these results raise issues regarding the safety of the blood supply.